Detergent effects on membranes at subsolubilizing concentrations transmembrane lipid motion, bilayer permeabilization, and vesicle lysis/reassembly are independent phenomena - Ahyayauch, Hasna (Langmuir : the ACS journal of surfaces and colloids, 2010)
Soluble amphiphiles, or detergents, are known to produce a number of structural and dynamic effects on membranes, even at concentrations below those causing membrane solubilization (i.e. in the so-called stage I of detergent-membrane interaction). The main subsolubilizing detergent effects on membranes are transmembrane lipid motion (flip-flop), breakdown of the membrane permeability barrier (leakage), and vesicle lysis/reassembly. For a proper understanding of membrane solubilization by detergents, it is important to assess whether the various effects seen at subsolubilizing surfactant concentrations occur independently from each other or are interconnected by cause-effect relationships so that they can be interpreted as necessary steps in the overall process of solubilization. To answer this question, we have explored the three above-mentioned effects (i.e., flip-flop, leakage, and lysis/reassembly) apart from solubilization in model (large unilamellar vesicles) and cell (erythrocyte) membranes. Five structurally different surfactants, namely, chlorpromazine, imipramine, Triton X-100, sodium dodecylsulfate, and sodium deoxycholate have been used. Each of them behaves in a unique way. Our results reveal that lipid flip-flop, vesicle leakage, and vesicle lysis/reassembly occur independently between them and with respect to bilayer solubilization so that they cannot be considered to be necessary parts of a higher-order unified process of membrane solubilization by detergents